2016
DOI: 10.3390/ijms17010089
|View full text |Cite
|
Sign up to set email alerts
|

Survivin Modulates Squamous Cell Carcinoma-Derived Stem-Like Cell Proliferation, Viability and Tumor Formation in Vivo

Abstract: Squamous Cell Carcinoma-derived Stem-like Cells (SCC-SC) originate from alterations in keratinocyte stem cells (KSC) gene expression and sustain tumor development, invasion and recurrence. Since survivin, a KSC marker, is highly expressed in SCC-SC, we evaluate its role in SCC-SC cell growth and SCC models. Survivin silencing by siRNA decreases clonal growth of SCC keratinocytes and viability of total, rapidly adhering (RAD) and non-RAD (NRAD) cells from primary SCC. Similarly, survivin silencing reduces the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…Consistent with this, HIF-1α expression is lower in normal skin compared with cSCC tumors, wherein it is positively correlated with the ascending grades of cSCC 31 , 32 . In addition, HIF-1α also plays roles in the proliferation of cSCC stem-like cells 33 . However, the mechanism of HIF-1α being regulated and its relationship with HIF-1α-mediated glycolytic reprogramming in cSCC remain under explored.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, HIF-1α expression is lower in normal skin compared with cSCC tumors, wherein it is positively correlated with the ascending grades of cSCC 31 , 32 . In addition, HIF-1α also plays roles in the proliferation of cSCC stem-like cells 33 . However, the mechanism of HIF-1α being regulated and its relationship with HIF-1α-mediated glycolytic reprogramming in cSCC remain under explored.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GLI activity is not strictly dependent on the upstream SMO activation in tumor cells. Upregulated GLI proteins are associated with the invasive potential, epithelial-mesenchymal transition (EMT) and stemness of tumors [43,44]. Moreover, GLI2 is a direct activator of SOX2 transcription in telencephalic neuroepithelial cells and SOX2 expression decreases in the developing neuroepithelium of Gli2-deficient mice [4,45].…”
Section: Survivin Expression Hedgehog/gli Signaling Pathway and Canmentioning
confidence: 99%
“…Bcl-2 is a typical anti-apoptotic protein and Bcl-2 overexpression is common in SCC [19,20]. Survivin is associated with the immortality of cells, it is tumor-specific and is only expressed in tumors and embryonic tissues [21,22]. Previous studies have confirmed the existence of abnormal apoptosis in SCC and tumor apoptosis could be affected by many factors [23].…”
Section: Discussionmentioning
confidence: 99%